Implementation of a mobile court in the settlement of divorce cases at the Tuban Regency Religious Court - Syanaya Mela Abyta; Kasuwi Saiban; Sunarjo Sunarjo (University of Merdeka Malang, 2022)
The purpose of this study is to analyze the application of the Supreme Court Regulation Number 1 of 2014 concerning Guidelines for Legal Services for the Underprivileged in the Court in the settlement of divorce cases through a mobile court in the Tuban district religious court and to determine the inhibiting and supporting factors for the application of the Supreme Court Regulation Number 1 2014 concerning Guidelines for Legal Services for Underprivileged People in Courts in the settlement of divorce cases through a mobile court at the Tuban Regency religious court. This research is empirical legal research, using a sociological juridical research approach. Sources of data obtained from this study are primary data and secondary data. The data collection method was carried out by means of in-depth interviews and documentation, and the data analysis used in this study was a qualitative method. The mobile trial was held outside the Tuban Regency religious court building in order to provide legal services for people who live far from the court, in terms of transportation costs and the distance traveled is difficult to attend the trial at the court office. In the implementation of the mobile court, the types of cases that are prioritized to be tried are only mild cases, such as divorce cases, both divorced and divorced, and isbat marriage. The mobile court in a divorce case at the Tuban district religious court is usually carried out at the sub-district office or at the village hall office within the court's jurisdiction.